Discovery of novel prognostic tools to stratify high risk stage II colorectal cancer patients utilising digital pathology - Caie, Peter David (The University of Edinburgh, 2015)
Colorectal cancer (CRC) patients are stratified by the Tumour, Node and Metastasis (TNM) staging system for clinical decision making. Additional genomic markers have a limited utility in some cases where precise targeted therapy may be available. Thus, classical clinical pathological staging remains the mainstay of the assessment of this disease. Surgical resection is generally considered curative for Stage II patients, however 20-30% of these patients experience disease recurrence and disease specific death. It is imperative to identify these high risk patients in order to assess if further treatment or detailed follow up could be beneficial to their overall survival. The aim of the thesis was to categorise Stage II CRC patients into high and low risk of disease specific death through novel image based analysis algorithms. Firstly, an image analysis algorithm was developed to quantify and assess the prognostic value of three histopathological features through immuno-fluorescence: lymphatic vessel density (LVD), lymphatic vessel invasion (LVI) and tumour budding (TB). Image analysis provides the ability to standardise their quantification and negates observer variability. All three histopathological features were found to be predictors of CRC specific death within the training set (n=50); TB (HR =5.7; 95% CI, 2.38-13.8), LVD (HR =5.1; 95% CI, 2.04-12.99) and LVI (HR =9.9; 95% CI, 3.57- 27.98). Only TB (HR=2.49; 95% CI, 1.03-5.99) and LVI (HR =2.46; 95%CI, 1 - 6.05), however, were significant predictors of disease specific death in the validation set (n=134). Image analysis was further employed to characterise TB and quantify intra-tumoural heterogeneity. Tumour subpopulations within CRC tissue sections were segmented for the quantification of differential biomarker expression associated with epithelial mesenchymal transition and aggressive disease. Secondly, a novel histopathological feature ‘Sum Area Large Tumour Bud’ (ALTB) was identified through immunofluorescence coupled to a novel tissue phenomics approach. The tissue phenomics approach created a complex phenotypic fingerprint consisting of multiple parameters extracted from the unbiased segmentation of all objects within a digitised image. Data mining was employed to identify the significant parameters within the phenotypic fingerprint. ALTB was found to be a more significant predictor of disease specific death than LVI or TB in both the training set (HR = 20.2; 95% CI, 4.6 – 87.9) and the validation set (HR = 4; 95% CI, 1.5 – 11.1). Finally, ALTB was combined with two parameters, ‘differentiation’ and ‘pT stage’, which were exported from the original patient pathology report to form an integrative pathology score. The integrative pathology score was highly significant at predicting disease specific death within the validation set (HR = 7.5; 95% CI, 3 – 18.5). In conclusion, image analysis allows the standardised quantification of set histopathological features and the heterogeneous expression of biomarkers. A novel image based histopathological feature combined with classical pathology allows the highly significant stratification of Stage II CRC patients into high and low risk of disease specific death.
Keywords: digital pathology; image analysis; big data; colorectal cancer